The Study of Challenges and Issues of Blended Learning in High School Education during the Covid 19 Period: A Focus Group Discussion - Dusita Sirisakpanich, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Coronavirus (Covid-19) pandemic interrupted our lives, particularly education in Thailand. As a response to interruption of education due to the Covid-19 pandemic. The schools have been closed to prevent the spread of the virus, and they have converted their system into distance education. The purposes of this paper are to understand the perceptions of the teachers and students regarding the use of blended learning modes in teaching learning transactions and to determine the weaknesses and the strengths of the pandemicdistance education, educators may specify convenient methods and techniques for the following terms. A qualitative research approach for this study was chosen through focus groups viainternet software application. Two focus groups were convened in December 2021, to solicit current students and teachers‘ opinions on the blended learning education at Kasetsart University Laboratory School Center for Educational Research and Development. The findings revealed that a blended learning is relatively new to Thai Education system, therefore, it is important to review how a blended learning environment impacts an experience by teachers and students in the learning environment.During the COVID-19 pandemic, e-learning has turned into an important alternative for reforming the entire traditional education system. Effective teaching style of online interactions is very important for enhancing online interactions and motivating students to participate in online discussions. In addition to this, the use of technology in education is only to facilitate the teacher in transfer of knowledge, not on building the students‘ character.